2021
DOI: 10.3390/brainsci11091137
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Default Mode Network Connectivity in Resting-State fMRI in People with Mild Dementia Receiving Cognitive Stimulation Therapy

Abstract: Group cognitive stimulation therapy (CST) is a 7-week activity-based non-pharmacological intervention for people with mild to moderate dementia. Despite consistent evidence of clinical efficacy, the cognitive and brain mechanisms of CST remain unclear. Theoretically, group CST as a person-centred approach may work through promoting social interaction and personhood, executive function, and language use, especially in people with higher brain/cognitive reserve. To explore these putative mechanisms, structural M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 51 publications
3
11
0
2
Order By: Relevance
“…Regarding global cognition, the personalized and adapted program of CS achieved statistical significance between and within group improvements in the ND, SCI, and LD groups, post-intervention, and at months, and 12 months. Other authors found similar results between groups in participants with normal cognition (Polito et al, 2015;Schultheisz et al, 2018) and within group (P. Gamito et al, 2020;Park et al, 2019;Tarnanas et al, 2014); in participants with MCI bet-ween groups (Polito et al, 2015;Tsai et al, 2019), and within group (Llanero Luque et al, 2011), also including older adults from MCI to mild-to-moderate dementia bet-ween groups (J Alves et al, 2014) and within group (Kim et al, 2017) post-intervention; as well as an effect of interaction between session and group in participants with MCI (Moro et al, 2015) In agreement with our results, other authors also found no significant differences in participants with dementia, between groups (Capotosto et al, 2017;Liu et al, 2021;L贸pez et al, 2022), all of them administered adapted CS but with a higher number of sessions. Two of them applied participants living in a community and within group (Alvares-Pereira et al, 2021;J Alves et al, 2014;Capotosto et al, 2017;Cove et al, 2014;Gibbor et al, 2021;Justo-Henriques et al, 2021;L贸pez et al, 2022;Miranda-Castillo et al, 2013;Orrell et al, 2012;Orgeta et al, 2015), four of these studies applied to in younger aged older adults (J Alves et al, 2014;Cove et al, 2014;Justo-Henriques et al, 2021;Orgeta et al, 2015), and five administered adapted CS (Jorge Alves et al, 2014;Capotosto et al, 2017;Cove et al, 2014;Gibbor et al, 2021;…”
Section: Discussionsupporting
confidence: 88%
“…Regarding global cognition, the personalized and adapted program of CS achieved statistical significance between and within group improvements in the ND, SCI, and LD groups, post-intervention, and at months, and 12 months. Other authors found similar results between groups in participants with normal cognition (Polito et al, 2015;Schultheisz et al, 2018) and within group (P. Gamito et al, 2020;Park et al, 2019;Tarnanas et al, 2014); in participants with MCI bet-ween groups (Polito et al, 2015;Tsai et al, 2019), and within group (Llanero Luque et al, 2011), also including older adults from MCI to mild-to-moderate dementia bet-ween groups (J Alves et al, 2014) and within group (Kim et al, 2017) post-intervention; as well as an effect of interaction between session and group in participants with MCI (Moro et al, 2015) In agreement with our results, other authors also found no significant differences in participants with dementia, between groups (Capotosto et al, 2017;Liu et al, 2021;L贸pez et al, 2022), all of them administered adapted CS but with a higher number of sessions. Two of them applied participants living in a community and within group (Alvares-Pereira et al, 2021;J Alves et al, 2014;Capotosto et al, 2017;Cove et al, 2014;Gibbor et al, 2021;Justo-Henriques et al, 2021;L贸pez et al, 2022;Miranda-Castillo et al, 2013;Orrell et al, 2012;Orgeta et al, 2015), four of these studies applied to in younger aged older adults (J Alves et al, 2014;Cove et al, 2014;Justo-Henriques et al, 2021;Orgeta et al, 2015), and five administered adapted CS (Jorge Alves et al, 2014;Capotosto et al, 2017;Cove et al, 2014;Gibbor et al, 2021;…”
Section: Discussionsupporting
confidence: 88%
“…In line with this argumentation, multidomain interventions have already been shown to be effective in stimulating modifiable risk factors in parallel to delay the progression of dementia [ 314 , 379 , 382 ], even with existing structural changes in the brain [ 295 , 400 , 406 ]. To improve cognition, multidomain interventions should comprise at least three modalities, one of which is a cognitive approach [ 314 ].…”
Section: Discussionmentioning
confidence: 98%
“…Characteristically, people with dementia are involved in goal setting and support for carers is offered [ 1 , 2 , 7 , 24 , 25 , 291 , 292 ]. The underlying mechanisms of effective COT are ascribed to the use of cognitive reserve, enabling people with AD to maintain functions despite evident disease pathology [ 2 , 293 , 294 , 295 , 296 , 297 ]. Results of an functional magnetic resonance imaging study confirmed that despite a significant reduction in grey matter volume CST led in comparison to usual treatment to an increase in resting-state default mode network connectivity in the posterior cingulate cortex and bilateral parietal cortices in PwAD [ 295 ].…”
Section: Individual Approachesmentioning
confidence: 99%
“…In this Special Issue, several papers make use of functional neuroimaging data (fMRI) to derive connectivity: in particular, the papers by Chrobak et al [3], De Asis-Cruz et al [4], Khan et al [5], and Liu et al [6] are based on resting-state data, while only the paper by Tak et al [7] makes use of fMRI during a motor task (right-hand movement) together with dynamic causal modeling.…”
mentioning
confidence: 99%
“…Liu et al [6] analyzed subjects with mild dementia to understand the possible beneficial effects of cognitive stimulation therapy (a kind of therapy based on non-pharmacological interventions) on cognitive and brain mechanisms. To this end, they collected structural MRI and resting-state functional MRI data and evaluated connectivity through correlation and anticorrelation analysis.…”
mentioning
confidence: 99%